2019
DOI: 10.3389/fmars.2019.00753
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Growth Rates of the Mediterranean Mussel in a Coastal Lagoon Driven by Groundwater Inflow

Abstract: Groundwater discharge is today recognized as an important pathway for freshwater, nutrients and other dissolved chemical substances to coastal systems. While its effect on supporting primary production in coastal ecosystems is increasingly recognized, its impact on growth of animals at higher trophic level (primary and secondary consumers) is less well documented. Here, we investigate the impact of groundwater discharge on the growth of the Mediterranean mussel (Mytilus galloprovincialis) in a coastal lagoon. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 89 publications
(126 reference statements)
1
10
0
Order By: Relevance
“…field may have contributed to a different periodicity of tissue growth and shell accretion between the lab and field populations (Andrisoa et al, 2019;Karayücel et al, 2010;Okaniwa et al, 2010;Orban et al, 2002). Similar values of growth rates and condition index to those we recorded at Mutriku have been reported for M. galloprovincialis mussels grown in other coastal lagoons (Andrisoa et al, 2019).…”
Section: Discussionsupporting
confidence: 77%
“…field may have contributed to a different periodicity of tissue growth and shell accretion between the lab and field populations (Andrisoa et al, 2019;Karayücel et al, 2010;Okaniwa et al, 2010;Orban et al, 2002). Similar values of growth rates and condition index to those we recorded at Mutriku have been reported for M. galloprovincialis mussels grown in other coastal lagoons (Andrisoa et al, 2019).…”
Section: Discussionsupporting
confidence: 77%
“…The net flow, resulting from the inputs to and outputs from the Mediterranean Sea was calculated and integrated for the two years previous to the mussels sampling date (around 15 May). Andrisoa et al (2019) showed that the age of 3-4 cm mussels in this area may be around 2 years.…”
Section: It Is Precisely This Inflow Of Atlantic Water Through the St...mentioning
confidence: 81%
“…The 60 days pattern observed in the shell of the deep species Bathymodiolus thermophilus might reflect current velocity changes in the hydrothermal habitats induced by ridge-crest jets (Nedoncelle et al, 2013;Nedoncelle et al, 2015). The five and three days patterns of the mussel M. galloprovincialis observed in the Mediterranean lagoon of Salses-Leucate (France) could be due to regular wind events occurring in this area (Andrisoa et al, 2019).The two-day periodicity recorded in the shell of the tropical Comptopallium radula could be synchronised with temperature or sea level pressure as both of these parameters display two-day cycles (Thébault et al, 2006). Although a synchronism with environmental variables appears, the precise origin of growth increments is still discussed in literature.…”
Section: Shells As Biological Archivesmentioning
confidence: 92%